SISTEM EKOMONI MERUPAKAN KEADILAN SOSIAL SEBAGAI PANDANGAN BARU EKONOMI INDONESIA - Siswanto, Siswanto (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2006)
There are several alternatives of economic system that can be applied in Indonesia, including three well-known economic system : liberal/capitalism economic system, social economic system and mixed economic system.The monetary/economic crisis which hit Indonesia in 1997, has becomea multidimensional crisis. The major real economic sector which has survived during this time is the middle low sector white the social gap bicome widened. In relation with the application of economic system in Indonesia, the best economic system to be applied in Indonesia in the future is that based on social fairness.